Using Crisis Theory in Dealing With Severe Mental Illness–A Step Toward Normalization? - Baumgardt, Johanna; Weinmann, Stefan (Frontiers in Sociology, 2022)
The perception of mental distress varies with time and culture, e.g. concerning its origin as either social or medical. This may be one reason for the moderate reliability of descriptive psychiatric diagnoses. Additionally, the mechanisms of action of most psychiatric treatments and psychotherapeutic interventions are generally unknown. Thus, these treatments have to be labeled as mostly unspecific even if they help in coping with mental distress. The psychiatric concept of mental disorders therefore has inherent limitations of precision and comprises rather fuzzy boundaries. Against this background, many people question the current process of diagnosing and categorizing mental illnesses. However, many scholars reject new approaches discussed in this context. They rather hold on to traditional diagnostic categories which therefore still play a central role in mental health practice and research and. In order to better understand the adherence to traditional psychiatric concepts, we take a closer look at one of the most widely adopted traditional concepts – the Stress-Vulnerability Model. This model has originally been introduced to tackle some problems of biological psychiatry. However, it has been misapplied with the result of drawing attention preferentially to biological vulnerability instead of a wider array of vulnerability factors including social adversity. Thus, in its current use, the Stress-Vulnerability Model provides only a vague theory for understanding mental phenomena. Therefore, we discuss the advantages and allegedly limited applicability of Crisis Theory as an alternative heuristic model for understanding the nature and development of mental distress. We outline the problems of this theory especially in applying it to severe mental disorders. We finally argue that an understanding of Crisis Theory supported by a systemic approach can be applied to most types of severe psychological disturbances implying that such an understanding may prevent or manage some negative aspects of the psychiatrization of psychosocial problems.